Kabuki syndrome with ossification of the posterior longitudinal ligament requiring differentiation from Ehlers-Danlos syndrome: a case report with a literature review - 石田, 哲朗; Murayama, Tomonori (Brazilian Journal of Case Reports, 2022)
Kabuki syndrome (KS) comprises multiple congenital abnormalities and the main symptoms include characteristic facial features, skeletal and spinal abnormalities, and mental retardation. The estimated incidence of KS is 1 in 32000, and mutations in the KMT2D gene (also known as MLL2) are considered to be involved. The details of such mutations, including the mode of inheritance, are unclear. A 40-year-old woman visited our hospital with back pain and urinary incontinence. The patient had been diagnosed with Ehlers-Danlos syndrome (EDS) in childhood, on the basis of physical findings including hip subluxation. Because of her characteristic facial features, we suspected KS instead. Genetic testing revealed the presence of a rare missense mutation in KDM6A that was suggestive of KS. Computed tomography showed that she had ossification of the posterior longitudinal ligament (OPLL). On the basis of her clinical presentation and genetic mutation in KDM6A, we made a diagnosis of KS with OPLL. Hereditary diseases may share similar clinical characteristics, as in the case of our patient with Kabuki syndrome, who was misdiagnosed in childhood as having an Ehlers-Danlos syndrome involving disordered connective tissue. Physicians should undertake a comprehensive consideration of multiple clinical features when diagnosing a hereditary disease.